Molecular complexes of the triterpene glycosides with L-tyrosine and their biological activity - Yakovishin, L.A.; Lekar, A.V.; Vetrova, E.V.; Borisenko, N.I.; Borisenko, S.N.; Grishkovets, V.I. (Вiopolymers and Cell, 2012)
Aim. To investigate the complexation of L-tyrosine (Tyr) with hederagenin 3-O-α-L-rhamnopyranosyl-(1→2)-O-α-Larabinopyranoside (α-hederin) and its 28-O-α-L-rhamnopyranosyl-(1→4)-O-β-D-glucopyranosyl-(1→6)-O-β-D-glucopyranosyl ester (hederasaponin C); to study the effect of glycosides, Tyr, and their mixtures on Avena sativa L. seed germination. Methods. Electrospray ionization mass spectrometry. Results. Mass spectra of mixes of glycosides with Tyr have been received and interpreted. The comparative analysis of biological activity of individual glycosides and their complexes with Tyr and others aromatic amino acids has been performed. Conclusions. For the first time a composition of the complexes is established by mass spectrometry. The complex of hederin with Tyr has appeared most toxic.